Pembantaian Etnis Cina di Batavia 1740 Dampak Konflik Golongan "Prinsgezinden" dan "Staatsgezinden" di Belanda? - Suratminto, Lilie (Wacana, Journal of the Humanities of Indonesia, 2004)
From 9th to 10th of October 1740 the riot occurred in Batavia, which was followed by a terrible massacre of the Chinese ethnic. More than 10.000 Chinese were killed. This was the black page of the East Indies Companies history in Batavia. This paper revealed the background of the actors who had played an important role in the tragedy in Batavia in 1740. They were two nobleses groups that influenced the policy of the Republic of the Netherlands, namely the Orangi n (the people who agreed Orange family as their leader and the head of state) or the Prinsgezinden and the Staatgezinden as the other group who was more liberal and against the Orange family. Actually this massacre could be prevented if among those persons in the government had worked together and helped each other in resolving problems.